2007
DOI: 10.1139/x07-039
|View full text |Cite
|
Sign up to set email alerts
|

The photosynthetic response of American chestnut seedlings to differing light conditions

Abstract: Restoration attempts to reintroduce American chestnut trees to the eastern deciduous forest by means of a disease-resistant Chinese–American hybrid seed are in progress. Knowing the light conditions required for optimum seedling performance is necessary to maximize the success of reintroduction. American chestnut ( Castanea dentata (Marsh.) Borkh.) seedlings were planted in two replicate forests in Vinton County, Ohio, in areas that had been thinned (more available light) and in control areas (intact canopy, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…These same trends are similar to those found in a two-year old field study [19] and in an outdoor shade-house study [17]. Despite the low levels of growth in the midstory-removal treatment, survival rates in this treatment indicate chestnuts will meet photosynthetic demands under an intact forest overstory canopy for at least five growing seasons, similar to previous studies [16,20]. Our results support the observations of Paillet [42], who hypothesized that chestnut efficiently uses limited light resources through recurrent root-collar sprouting and advantageous growth once released.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These same trends are similar to those found in a two-year old field study [19] and in an outdoor shade-house study [17]. Despite the low levels of growth in the midstory-removal treatment, survival rates in this treatment indicate chestnuts will meet photosynthetic demands under an intact forest overstory canopy for at least five growing seasons, similar to previous studies [16,20]. Our results support the observations of Paillet [42], who hypothesized that chestnut efficiently uses limited light resources through recurrent root-collar sprouting and advantageous growth once released.…”
Section: Discussionsupporting
confidence: 88%
“…Pure American chestnut seedlings respond positively to increased light in the field and under controlled environmental conditions [15][16][17][18]. Chestnut seedlings had similar or better survival in shaded conditions compared to openings receiving full sunlight [15,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although chestnut is classified as moderately shadetolerant (Joesting et al 2007, Joesting et al 2009), in its new position as an understory tree, shade has a major effect on chestnut's competitive ability. Studies have suggested that current chestnut growth and abundance are greater on sites with higher light availability (Paillet 1988, Griffin 1989, Griffin 1992.…”
Section: Discussionmentioning
confidence: 99%
“…There is disagreement regarding the shade tolerance classification of American chestnut (McCament and McCarthy, 2005;Wang et al, 2006;Joesting et al, 2007). American chestnut seedlings and saplings are capable of surviving in the shade, much like the ''sit and wait'' strategy of shade tolerant species (Paillet, 1993).…”
Section: Introductionmentioning
confidence: 99%